A "roadmap" for Kashmir? - Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2005)
The commencement of bus services between the Indian and Pakistani parts of Kashmir on April 7, 2005, and the visit to India by the Pakistani President Pervez Musharraf from April 16 - 18 have given a definite boost to the process of rapprochement between the two countries. In their joint final communiqué, both sides emphasized that they considered the peace process irreversible. They also discussed new approaches to resolving the Kashmir conflict which show signs of an emerging 'roadmap.' These developments give cause for hope that the spirit of reconciliation that has existed since April 2003 will bring about a lasting improvement in Indian-Pakistani relations. The success of the initiative will depend on whether Musharraf can push it through against domestic resistance in Pakistan. (SWP Comments / SWP)
Keywords: 320